2019
DOI: 10.1080/00016357.2019.1656819
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic antibiotics for staged bone augmentation in implant dentistry

Abstract: Background: The objective of the study was to assess the effect of prophylactic antibiotics on the outcome of bone augmentation and subsequent dental implant placement by combining the recommended quality assessment methods for systematic reviews and primary studies. Materials and methods: This is a complex systematic review in which systematic reviews as well as primary studies are scrutinised. A search of Medline (OVID), The Cochrane Library (Wiley) and EMBASE, PubMed and Health technology assessment (HTA) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Implant dentistry is a prosthetic effort via a surgical procedure [32,33]. In order to achieve an ideal prosthetic construct, precise plan should be taken into consideration prior to the beginning of treatment.…”
Section: Dental Implantmentioning
confidence: 99%
“…Implant dentistry is a prosthetic effort via a surgical procedure [32,33]. In order to achieve an ideal prosthetic construct, precise plan should be taken into consideration prior to the beginning of treatment.…”
Section: Dental Implantmentioning
confidence: 99%
“…Similarly, since the use of hemostatic materials or sutures (C3) in non-surgical extractions does not increase the risk of SSI [ 12 ], the use of antibiotics is not justified, as indicated by 82.2% of the participants. Conversely, in the case of ridge preservation procedures with bone grafting (C4), 83.4% of participants agreed on the need for antibiotics, though literature data are scarce and conflicting on this issue [ 39 , 40 ], and it has been suggested that a single preoperative dose (2 or 3 g of amoxicillin) would be sufficient to prevent SSI after bone regeneration procedures [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…After full-text assessment, 7 were included in qualitative synthesis. First, all articles that did not analyze the infection clinically Excluded: no control group with placebo or without treatment Bone grafts along with implant placement Lindeboom JA, 2005 [18] Excluded: no control group with placebo or without treatment Lindeboom JA, 2006 [19] Excluded: no control group with placebo or without treatment Klinge A, Khalil D, Klinge B et all 2020 [20] Excluded: It is a review Orthognathic surgery Lindeboom JA, Baas EM, Kroon FH 2003 [21] Excluded: no control group with placebo or without treatment Baqain ZH, Hyde N, Patrikidou A, Harris M.2004 [22] Excluded: no control group with placebo or without treatment Davis CM, Gregoire CE, Davis I, Steeves TW.2017 [23] Excluded: no control group with placebo or without treatment Oncologic surgery Righi M, Manfredi R, Farneti G, et all 1995 [24] Excluded: no control group with placebo or without treatment Head and neck surgery Mann W, Maurer J, Wolfensberger M, et all 1990 [25] Excluded: no control group with placebo or without treatment Clayman GL, Raad II, Hankins PD et all 1993 [26] Excluded: no control group with placebo or without treatment Endodontic procedure Raslan N, Mansour O, Assfoura L. 2017 [27] Excluded: no control group with placebo or without treatment Endodontic surgery Lindeboom JA, Frenken JW, Valkenburg et all 2005 [28] Included Dental extraction Laird WR 1972 [29] Excluded: no control group with placebo or without treatment Bystedt 1980 [30] Excluded: did not report data in a form suitable for inclusion Kupfer 1995 [15] Excluded: it is not a RCT Poeschl 2003 [31] Included &Foy SP, Shugars DA, Phillips C, et all 2004 [32] Excluded: did not report data in a form suitable for inclusion a Halpern LR,0.2007 [12] Included Kaczmarzyk 2007 [33] Included Adde, 2012 [34] Included *Hamiti-Krasniqi 2014 [35] Included Xue 2014 [36] Excluded: patients included in another study. It was not possible to contact the authors to confirm this Xue 2015 [13] Excluded: did not report data in a form suitable for inclusion Kaposvári 2017 [37] Included were excluded.…”
Section: Study Selectionmentioning
confidence: 99%